2020
DOI: 10.23736/s0393-2249.19.03583-5
|View full text |Cite
|
Sign up to set email alerts
|

Robotic partial nephrectomy versus radical nephrectomy in elderly patients with large renal masses

Abstract: BACKGROUND: Recent evidence suggests that the "oldest old" patients might benefit of partial nephrectomy (PN), but decision-making for this subset of patients is still controversial. aim of this study is to compare outcomes of robotic partial (rPN) or radical nephrectomy (rrN) for large renal masses in patients older than 65 years. METHODS: We identified 417≥65 years old patients who underwent RRN or RPN for cT1b or ≥cT2 renal mass at 17 high volume centers. Propensity score match analysis was performed adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Recent propensity-matched comparisons have demonstrated that robotic partial nephrectomy for large (>7 cm) clinical T2a masses has similar safety profile and 5-year oncological outcomes compared to MI-RN with the added benefit of renal function preservation and improved 5-year freedom from stage 3 chronic kidney disease (109). Similar findings have been reported in the elderly population (110). With burgeoning expertise in complex robotic partial nephrectomy for large renal masses, the role of MI-RN for localized renal masses may become increasingly limited in the future.…”
Section: Future Perspectives In Mi-rnsupporting
confidence: 78%
“…Recent propensity-matched comparisons have demonstrated that robotic partial nephrectomy for large (>7 cm) clinical T2a masses has similar safety profile and 5-year oncological outcomes compared to MI-RN with the added benefit of renal function preservation and improved 5-year freedom from stage 3 chronic kidney disease (109). Similar findings have been reported in the elderly population (110). With burgeoning expertise in complex robotic partial nephrectomy for large renal masses, the role of MI-RN for localized renal masses may become increasingly limited in the future.…”
Section: Future Perspectives In Mi-rnsupporting
confidence: 78%
“…years paved the way for the gradually increased employment of minimally invasive approaches, first with the advent of laparoscopy and then with robotics, progressively minimizing the impact and invasiveness of surgical procedures [7][8][9].…”
mentioning
confidence: 99%
“…There are several advantages of robotic technology to renal surgery, including an enhanced degree of freedom, three-dimensional visualization, higher magnification, surgeon’s ergonomics, the use of fluorescence imaging, and the elimination of tremors leading to a widespread utilization to perform more complex surgeries [ 5 , 6 , 7 , 8 , 9 , 10 ]. However, there is a potential risk for catastrophic complications during complex robotic renal surgery due to the close proximity of vital vascular structures [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%